Abrasive containing α-alumina particles and method for producing same
Patent Information
- Application Number
- JP2023507259
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-07
- Filing Date
- 2021-09-16
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2041-09-16
AI Technical Summary
【0013】 本発明の研磨材に含まれたα-アルミナ粒子は、構造式1の前駆体粉末から製造されて多面体結晶構造を有しながら所定の粒子サイズと密度範囲とを満足することにより、研磨工程時に、スクラッチの発生を最小化しながら研磨スラリー内の分散性に優れて研磨速度を向上させうる。
Smart Images

Figure 0007636035000009 
Figure 0007636035000010 
Figure 0007636035000001
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0129674, filed on October 7, 2020, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to an abrasive containing α-alumina particles having a polyhedral crystal structure that improves polishing efficiency, and a method for producing the same. [Background technology]
[0003] Alumina (Al2O3) has excellent mechanical strength such as abrasion resistance, chemical stability, thermal conductivity, and heat resistance, and is used in a wide range of areas such as abrasives, electronic materials, heat dissipation fillers, optical materials, and biomaterials. α-alumina is mainly used in the polishing process to flatten the surface and edges of ultra-thin glass used as a part of electronic devices such as OLEDs, PDPs, LCDs, and mobile phones, but in order to improve the polishing speed, it is necessary to control the physical properties such as particle shape and size of α-alumina used as an abrasive.
[0004] Alumina can generally be produced using bauxite as a raw material. For example, according to the Bayer process, aluminum hydroxide (gibbsite) or transition alumina is first obtained from the raw material bauxite, and then calcined in air to produce alumina powder. However, the alumina produced by the Bayer process is difficult to control in terms of particle shape and size, and is not suitable for all applications.
[0005] Meanwhile, Korean Patent Publication No. 10-2014-0130049 (Merck Patent GMBH) discloses that an aluminum hydroxide particle is obtained by adding an alkali metal salt (e.g., sodium sulfate, potassium sulfate) as a mineralizer to an aqueous solution or slurry of an aluminum salt, and then a phosphorus compound and an arbitrary dopant are added thereto and then calcined to produce α-Al2O3 flakes, and the α-Al2O3 flakes have a thickness of less than 0.5 μm and a diameter of 15 to 30 μm.50 Alpha-alumina having such particle size and thickness conditions is a plate-shaped particle with a large length-to-width ratio (ratio of diameter / thickness), and such plate-shaped particles, when used as an abrasive, have a high risk of causing scratches and sink in the slurry, resulting in poor dispersibility, making them unsuitable for the polishing process of electronic device parts such as ultra-thin glass.
[0006] Therefore, in order to use an alumina material in polishing a thin film, etc., a technique is required that realizes a particle shape and size that can reduce the occurrence of scratches and improves dispersibility in the polishing slurry. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Korean Patent Publication No. 10-2014-0130049 Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide an abrasive containing α-alumina particles having a crystal structure and physical properties that minimize the occurrence of scratches and have excellent dispersibility in abrasive slurry to improve polishing efficiency, and a method for manufacturing the same. [Means for solving the problem]
[0009] One aspect of the present invention is an abrasive containing α-alumina particles having a polyhedral crystal structure, the α-alumina particles having an average particle size (D 50 The abrasive has a surface area of 300 nm to 10 μm, a bulk density of 0.2 to 0.5 g / ml, the α-alumina particles have a crystal structure in which the <0001> plane occupies 10 to 20% of the total crystal surface area, and the content of the α-alumina particles is 85 to 100 wt % based on the total weight.
[0010] Another aspect of the present invention is a method for producing an abrasive material comprising the α-alumina particles, comprising the steps of: (Step S1) mixing and reacting an aqueous solution containing one or more aluminum salts with an aqueous solution containing a pH adjuster, and filtering and drying the product to obtain a precursor powder represented by the following structural formula 1; (Step S2) adding the precursor powder together with a fluorine-based mineralizer to a dispersion medium and stirring; and (Step S3) filtering and drying the product of step S2, and then calcining the same to obtain a powder of α-alumina particles having a polyhedral crystal structure;
[0011] [Structural formula 1] TIFF0007636035000001.tif35168
[0012] Yet another aspect of the present invention provides a polishing method, comprising polishing an ultra-thin glass film used as a part of an electronic device with an abrasive containing the α-alumina particles. Effect of the Invention
[0013] The α-alumina particles contained in the abrasive of the present invention are prepared from the precursor powder of structural formula 1 and have a polyhedral crystal structure while satisfying a predetermined particle size and density range, thereby minimizing the generation of scratches during the polishing process and providing excellent dispersibility in the polishing slurry, thereby improving the polishing rate. [Brief description of the drawings]
[0014] [Figure 1] 1 is a scanning electron microscope (SEM) photograph of the α-alumina particles produced in Example 1. [Diagram 2] 1 is a diagram showing the results of X-ray diffraction analysis (XRD) of the α-alumina particles produced in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Since the present invention can be modified in various ways and has various embodiments, specific embodiments are illustrated in the drawings and described in detail in the detailed description. However, this is not intended to limit the present invention to the specific embodiment, but should be understood to include any modifications, equivalents, or alternatives within the spirit and technical scope of the present invention. In describing the present invention, if it is determined that a detailed description of related publicly known technology may obscure the gist of the present invention, the detailed description will be omitted.
[0016] The present invention will now be described in more detail.
[0017] One embodiment of the present invention relates to an abrasive comprising α-alumina particles having a polyhedral crystal structure.
[0018] The α-alumina particles having the polyhedral crystal structure have a shape close to a sphere, which means that, for example, the ratio (D / H) of the diameter (D) perpendicular to the <0001> plane, which is the crystallographic C-plane, to the height (H) parallel to said diameter (D) is close to 1.
[0019] In particular, the α-alumina particles according to the present invention may have a tetradecahedral crystal structure in which the <0001> plane occupies 10-20%, specifically 15-20%, of the total crystal surface area. If the <0001> plane area is less than 10%, the particles will be rod-shaped, and if it exceeds 20%, the particles will be nearly plate-shaped. Such α-alumina particles having a nearly spherical polyhedral crystal structure, when used as an abrasive, can minimize the occurrence of scratches and improve the polishing performance compared to plate-shaped or amorphous particles. The term "amorphous" refers to an irregular state in which the outer shape is not uniform, and is distinguished from the polyhedral crystal structure of the present invention, which has a clear crystal surface.
[0020] The α-alumina particles having the polyhedral crystal structure have an average particle size (D 50 ) is 300 nm to 10 μm and the density is 0.2 to 0.5 g / ml.
[0021] D50 is a median value of the particle size distribution measured by a method commonly used in the art, for example, by using a laser particle size analyzer. In the present invention, D 50 The fineness is 300 nm to 10 μm, and the generation of scratches during polishing can be minimized at the fine level while providing a desired level of polishing speed, thereby improving polishing efficiency.
[0022] The density can be measured by a method commonly used in the art, for example, as the mass required to fill a volume of 100 mL using a measuring cylinder. In the present invention, when the density of the α-alumina particles satisfies 0.2 to 0.5 g / mL, the particles do not sink in the polishing slurry and are uniformly dispersed, thereby improving the polishing efficiency.
[0023] The abrasive according to the present invention contains 85% by weight or more, i.e., 85-100% by weight, of α-alumina particles having the above physical properties based on the total weight. If the content of the α-alumina particles is less than 85% by weight, it is difficult to ensure a desired level of polishing speed during polishing work.
[0024] In addition, the abrasive according to the present invention is used for polishing in the form of a water-dispersed slurry in which the abrasive is dispersed in water. The slurry in which the abrasive is dispersed in water has a viscosity in the range of 1 to 10 pcs, specifically, 1 to 5 pcs. When the viscosity is within the range, the polishing efficiency can be improved while maintaining a balance in which α-alumina particles are uniformly dispersed.
[0025] Another embodiment of the present invention relates to a method for producing an abrasive material containing the α-alumina particles having the polyhedral crystal structure. The method will be described below step by step.
[0026] First, an aqueous solution containing one or more aluminum salts and an aqueous solution containing a pH adjuster are mixed and reacted with each other (Step S1).
[0027] The aluminum salt includes aluminum sulfate (Al2(SO4)3·4~18H2O), aluminum nitrate (Al(NO3)3·9H2O), aluminum acetate (Al(CHCOO)3OH) or a mixture thereof, and is dissolved in heated water (e.g., about 60°C) at a concentration of 5~30% to prepare an aqueous solution for complete dissolution.
[0028] The pH adjuster includes sodium carbonate (Na2CO3), sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium carbonate (CaCO3) or a mixture thereof, and is dissolved in heated water (e.g., about 40°C) at a concentration of 5 to 30% to prepare an aqueous solution for complete dissolution.
[0029] The aluminum salt aqueous solution and the pH adjuster aqueous solution may be mixed at a constant rate (e.g., 25 mL / min) to carry out a sol-gel reaction at a temperature ranging from room temperature to 95° C. The pH of the reactant ranges from 6 to 10.
[0030] Through the above reaction, a precursor of the following structural formula 1 is produced:
[0031] [Structural formula 1] TIFF0007636035000002.tif35168
[0032] The precursor of formula 1 is pseudo-boehmite, whose chemical composition is expressed as AlO(OH), and has a high water content because water (HO) is bound to an octahedral unit cell, resulting in a small crystallite size.
[0033] This precursor is formed under lower pH conditions than aluminum hydroxide (Al(OH)3), which is the main starting material used in the conventional alumina production. When it is subsequently transformed into α-Al2O3 through a high-temperature calcination process, it is advantageous to obtain a polyhedral crystal structure because the seed-induced particle aggregation and phase transition occur at a relatively low temperature.
[0034] The precursor is produced as a solid, which is filtered, washed and dried to obtain a powder.
[0035] Furthermore, the obtained powder can be used in the subsequent steps after being pulverized, which is carried out by a ball mill dry pulverization method, etc., to obtain powder with a size of 300 nm to 20 μm.
[0036] Subsequently, the precursor powder is added to a dispersion medium together with a fluorine-based mineralizer and stirred (step S2).
[0037] The fluorine-based mineralizer is an additive for growing the crystals of α-alumina particles, and LiF2, AlF3, NaF, NaPF6, K2TiF6 or a mixture thereof is used.
[0038] When used in excess, such fluorine-based mineralizers may remain in the final α-alumina or form agglomerates during the firing process. To minimize such drawbacks, it is advantageous to use the precursor powder and the fluorine-based mineralizer in a weight ratio of 100:0.1 to 100:2, more preferably 100:0.5 to 100:1.5.
[0039] The dispersion medium is for wet dispersion of the precursor powder and the fluorine-based mineralizer, and may be, for example, ethanol, methanol, acetone, isopropyl alcohol, or a mixture thereof. The wet dispersion affects the polyhedral crystal structure of the final α-alumina particles by uniformly dispersing the fluorine-based mineralizer and minimizing the agglomeration of the precursor (pseudoboehmite) particles.
[0040] The dispersion medium is used in an amount of 2 to 5 times the weight of the precursor powder, but is not limited thereto.
[0041] The stirring is carried out for 20 to 60 minutes to uniformly mix the precursor powder and the fluorine-based mineralizer.
[0042] After stirring, the product is filtered, dried, and then calcined to obtain a powder of α-alumina particles having a polyhedral crystal structure (step S3).
[0043] The calcination is a process of melting and synthesizing dry powders of the precursor powder and the fluorine-based mineralizer at high temperatures in a crucible made of high-purity alumina or zirconia.
[0044] Specifically, the firing is performed by increasing the temperature at 3 to 15° C. / min, and then maintaining the temperature at 800 to 1000° C. for 2 to 5 hours. Meanwhile, the firing conditions can be appropriately changed in consideration of the reaction and volatility due to the difference in melting point between each material of the mixture, and the amount of heat required for synthesis.
[0045] In the above process, the α-alumina particles prepared by using the pseudoboehmite precursor of formula 1 have high purity and contain 98.5% by weight or more of Al components when analyzed by XRF (X-ray fluorescence).
[0046] Moreover, as described above, the α-alumina particles have a polyhedral crystal structure with a ratio of
[0001] faces of 10 to 20% and an average particle size (D 50 ) and a density of 0.2 to 0.5 g / mL, an abrasive containing 85% or more by weight thereof can minimize the occurrence of scratches and has excellent dispersibility in the polishing slurry, thereby improving the polishing efficiency.
[0047] For example, when the α-alumina particle abrasive is supplied in the form of an aqueous dispersion slurry at a rate of 150 mL / min and ultra-thin glass used as a component of electronic devices is polished at a pressure of 3.5 psi for 60 seconds, the polishing rate measured as the difference in thickness before and after polishing is as high as 4000 to 8000 Å / min. EXAMPLES
[0048] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to specific examples so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein.
[0049] Example 1 Aqueous solution (a) was prepared by completely dissolving 199.8g of Al2(SO4)3·14~18H2O in 982.8g of pure water heated at 60℃, and aqueous solution (b) was prepared by completely dissolving 95.4g of Na2CO3 in 528g of pure water heated at 40℃. Aqueous solution (b) was added to aqueous solution (a) at a rate of 25mL / min and stirred for 10 minutes to react. The reaction product (pH 7.3~7.8) was filtered, washed, dried, and then pulverized to obtain the precursor powder of pseudoboehmite.
[0050] 40 g of the precursor powder and 0.2 g of AlF3 were mixed in 120 g of ethanol and stirred for 30 minutes.
[0051] The obtained product was then filtered and dried, and then heat-treated at 900° C. for 5 hours with a temperature increase rate of 1° C. / min to obtain α-alumina powder.
[0052] Example 2 The same procedure as in Example 1 was carried out, except that AlF3 was used at a content of 0.4 g.
[0053] Example 3 The same procedure as in Example 1 was carried out, except that AlF3 was used at a content of 0.6 g.
[0054] Comparative Example 1 40g of Al(OH)3 powder and 0.2g of AlF3 were dry mixed. The mixed powder was heat-treated and sintered at 900℃ for 5 hours with a temperature increase rate of 10℃ / min. After the heat treatment, α-alumina particle powder was finally obtained.
[0055] Comparative Example 2 The same procedure as in Comparative Example 1 was carried out, except that AlF3 was used at a content of 0.4 g.
[0056] Comparative Example 3 The same procedure as in Comparative Example 1 was carried out, except that AlF3 was used at a content of 0.8 g.
[0057] Comparative Example 4 The same procedure as in Comparative Example 1 was carried out, except that AlF3 was used at a content of 1.6 g.
[0058] Comparative Example 5 40g of Al(OH)3 powder and 0.2g of AlF3 were mixed in 120g of ethanol and stirred for 30 minutes. The obtained product was filtered and dried, and then heat-treated at 900℃ for 5 hours with a temperature increase rate of 10℃ / min. After the heat treatment, α-alumina particle powder was finally obtained.
[0059] Comparative Example 6 The same procedure as in Comparative Example 5 was carried out, except that AlF3 was used at a content of 0.3 g.
[0060] Comparative Example 7 The same procedure as in Comparative Example 5 was carried out, except that AlF3 was used at a content of 2 g.
[0061] Example 4 Aqueous solution (a) was prepared by completely dissolving 199.8g of Al2(SO4)3·14~18H2O in 982.8g of pure water heated at 60℃, and aqueous solution (b) was prepared by completely dissolving 72g of NaOH in 528g of pure water heated at 40℃. Aqueous solution (b) was added to aqueous solution (a) at a rate of 25mL / min and stirred for 10 minutes to react. The reaction product (pH 7.3~7.8) was filtered, washed, dried, and then pulverized to obtain the precursor powder of pseudoboehmite.
[0062] 40 g of the precursor powder and 0.2 g of AlF3 were mixed in 120 g of ethanol and stirred for 30 minutes.
[0063] The obtained product was then filtered and dried, and then heat-treated at 900° C. for 5 hours with a temperature increase rate of 10° C. / min to obtain α-alumina powder.
[0064] Comparative Example 8 Aqueous solution (a) was prepared by completely dissolving 199.8g of Al2(SO4)3·14~18H2O in 982.8g of pure water heated at 60℃, and aqueous solution (b) was prepared by completely dissolving 72g of NaOH in 528g of pure water heated at 40℃. Aqueous solution (b) was added to aqueous solution (a) at a rate of 25mL / min and stirred for 10 minutes to react. The reaction product (pH 7.3~7.8) was filtered, washed, dried, and then pulverized to obtain the precursor powder of pseudoboehmite.
[0065] 40 g of the precursor powder and 30.2 g of AlF were dry-mixed. The mixed powder was heat-treated and sintered at 900° C. for 5 hours with a temperature increase rate of 10° C. / min. After the heat treatment, α-alumina particle powder was finally obtained.
[0066] Comparative Example 9 The same procedure as in Comparative Example 8 was carried out, except that AlF3 was used at a content of 0.4 g.
[0067] Comparative Example 10 The same procedure as in Comparative Example 8 was carried out, except that AlF3 was used at a content of 0.8 g.
[0068] Comparative Example 11 The same procedure as in Comparative Example 8 was carried out, except that AlF3 was used in an amount of 1.6 g.
[0069] The physical properties of the α-alumina particles prepared in the above examples and comparative examples were measured and are shown in Table 1 below.
[0070] [Table 1]
[0071] As can be seen from Table 1, the α-alumina particles produced by wet mixing pseudoboehmite with a fluorine-based mineralizer and then calcining the mixture had a D 50 The thickness ratio of the polyhedral crystal structure is close to 1, while the D 50And the density of 0.2~0.5g / ml was satisfied.
[0072] [Experimental Example 1] Evaluation of crystal plane and purity of α-alumina particles The α-alumina particles having a polyhedral crystal structure produced in Example 1 were observed with a scanning electron microscope (SEM), and the results are shown in FIG.
[0073] 1, it can be seen that the α-alumina particles of Example 1 have a tetradecahedral crystal structure. Furthermore, as a result of image analysis of the SEM photograph, it was confirmed that the area of the c-plane (0001 plane) in the crystal structure was 15 to 20% of the total area.
[0074] In addition, the α-alumina particles of Example 1 were subjected to X-ray diffraction analysis (XRD) and X-ray fluorescence analysis (XRF), and the results are shown in FIG. 2 and Table 2, respectively.
[0075] [Table 2]
[0076] From Table 2 and FIG. 2, it can be seen that the α-alumina particles of Example 1 contain 98.5% by weight or more of an Al component and have a high purity.
[0077] Furthermore, the results of an ICP-OES (Inductively Coupled Plasma Optical Emission Spectrometry) analysis of the α-alumina particles of Example 1 are shown in Table 3 below.
[0078] [Table 3]
[0079] From Table 3, it can be confirmed that the α-alumina particles of Example 1 are of high purity.
[0080] [Experimental Example 2] Evaluation of polishing speed An experiment was carried out to compare the polishing rate of the tetradecahedral α-alumina particles (15-20% of
[0001] faces) of Example 1 with that of other companies' products having different morphologies.
[0081] Specifically, each abrasive to be compared was dispersed in water to prepare a slurry (solid content: 40-45% by weight), and the slurry was polished on an 8-inch polishing machine (Mirra, manufactured by AMAT). TM The surface of a glass (ultra-thin glass) substrate was polished for 60 seconds at a pressure of 3.5 psi using a polishing machine. The abrasive slurry was supplied at a rate of 150 mL / min, the rotation speed of the upper platen wafer head was 100 rpm, and the rotation speed of the lower platen was 110 rpm. In addition, an "IC1000 / suba IV stacked pad" (Rodel) was used as the pad.
[0082] After polishing, the polishing rate (Å / min) was measured by comparing the thickness of the polished film with that before polishing, and the results are shown in Table 4 below.
[0083] [Table 4]
[0084] From Table 4, it can be seen that the polyhedral crystal structure has a D of 300 nm to 10 μm. 50 The α-alumina particles of Example 1, which simultaneously satisfied the requirements of 0.2 to 0.5 g / mL and density, demonstrated the best polishing rate.
[0085] On the other hand, a comparative experiment was conducted on the polishing speed depending on the ratio of the tetradecahedral α-alumina particles (15-20%
[0001] faces) of Example 1 contained in the abrasive, and the polishing process was carried out as described above. The results are shown in Table 5 below.
[0086] [Table 5]
[0087] From Table 5, it can be seen that the polishing rate increases as the ratio of α-alumina particles having a
[0001] plane area of 15 to 20% increases (85% or more of the total abrasive).
[0088] Although the specific parts of the present invention have been described in detail above, it is obvious to those skilled in the art that such specific descriptions are merely preferred embodiments and do not limit the scope of the present invention. Therefore, the substantial scope of the present invention is defined by the claims and their equivalents.
Claims
1. A method for producing an abrasive containing α-alumina particles having a polyhedral crystal structure, comprising: (Step S1) mixing and reacting an aqueous solution containing one or more aluminum salts with an aqueous solution containing a pH adjuster, filtering and drying the product to obtain a precursor powder represented by the following structural formula 1; (Step S2) adding the precursor powder together with a fluorine-based mineralizer to a dispersion medium and stirring the mixture; and (Step S3) filtering and drying the product of Step S2, followed by calcining the product to obtain a powder of α-alumina particles having a polyhedral crystal structure; The α-alumina particles have an average particle size (D 50 ) of 300 nm to 10 μm and a density of 0.2 to 0.5 g / mL; In the α-alumina particles, the [0001] plane in the crystal structure occupies 10 to 20% of the total crystal plane area, The content of the α-alumina particles is 85 to 100 wt % based on the total weight.
2. The aluminum salt used in step S1 is aluminum sulfate (Al 2 (SO 4 ) 3 ・4 to 18 hours 2 O), aluminum nitrate (Al(NO 3 ) 3 ・9H 2 O), aluminum acetate (Al(CHCOO) 3 10. The method of claim 1, further comprising:
3. The pH adjuster used in step S1 is sodium carbonate (Na 2 CO 3 ), sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium carbonate (CaCO 3 2. The method of claim 1 , comprising:
4. The method according to claim 1 , wherein the mixing reaction in step S1 is carried out at a temperature ranging from room temperature to 95° C.
5. The method of claim 1, wherein in step S2, the precursor powder and the fluorine-based mineralizer are used in a weight ratio of 100:0.1 to 100:
2.
6. In step S2, the fluorine-based mineralizer is LiF 2 , AlF 3 , NaF, NaPF 6 , K 2 TIF 6 or a mixture thereof.
7. 2. The method according to claim 1, wherein the dispersion medium in step S2 comprises ethanol, methanol, acetone, isopropyl alcohol, or a mixture thereof.
8. The method according to claim 1, wherein the firing in step S3 is performed by increasing the temperature to 3 to 15° C. / min and then maintaining the temperature at 800 to 1000° C. for 2 to 5 hours.
9. 2. The method of claim 1, wherein the α-alumina particles obtained in step S3 contain 98.5 wt % or more of an Al component when analyzed by XRF.
10. A polishing method comprising polishing an ultra-thin glass film used as a part of an electronic device with an abrasive containing α-alumina particles produced by the method according to claim 1.
11. 11. The polishing method according to claim 10, wherein the polishing is performed for 60 seconds by supplying an abrasive in the form of an aqueous dispersion slurry at a rate of 150 mL / min and a pressure of 3.5 psi, and the polishing rate measured based on the difference in thin film thickness before and after polishing is in the range of 4000 to 8000 Å / min.
Citation Information
Patent Citations
Alpha-alumina powder and its production
JP1995206430A
POLYHEDRAL alpha-ALUMINA AND ITS MANUFACTURING METHOD
JP2008127257A
α-Alumina Flakes
KR1020140130049A
Polishing material, method for producing same, and polishing material composition
WO2016024624A1